Deke Mclelland's look & learn Photoshop 6 - McClelland, Deke, 1962- (Calif : IDG Books Worldwide, 2001)
1. Photoshop (Computer file). 2. Computer graphics.
Includes index.
Basic ed. students
Keywords: Adobe Photoshop; Computer graphics